2001
DOI: 10.1024//0044-3514.32.3.152
|View full text |Cite
|
Sign up to set email alerts
|

Risk Management in Consumers' Credit Decision Making

Abstract: Summary: A study is described of the risk management strategies employed by consumers who have made a purchase by credit. Realistic scenarios involving the purchase of consumer durables were used and adults with a variety of occupations and a range of experience of credit participated (N = 96). They were presented with minimal descriptions of alternative credit offers and an option to buy insurance to cover repayment difficulties due to job loss or illness. Participants could request any information required w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…For example, prior experience with negative events such as flooding is related to the intention to buy natural catastrophe insurance (Kunreuther et al, 1978; Zaleskiewicz, Piskorz, & Borkowska, 2002). Ranyard, Hinkley, and Williamson (2001) found that risk management strategies in buying consumables using credit depended on prior experience and emotional reactions. We expected statements concerning specific background knowledge and prior experience to be important elements for the decision maker.…”
Section: Main Studymentioning
confidence: 99%
“…For example, prior experience with negative events such as flooding is related to the intention to buy natural catastrophe insurance (Kunreuther et al, 1978; Zaleskiewicz, Piskorz, & Borkowska, 2002). Ranyard, Hinkley, and Williamson (2001) found that risk management strategies in buying consumables using credit depended on prior experience and emotional reactions. We expected statements concerning specific background knowledge and prior experience to be important elements for the decision maker.…”
Section: Main Studymentioning
confidence: 99%